In defence of October : speech delivered in Copenhagen in November 1932 - Trotski, Leon ([Colombo?] : Bolshevik-Samasamaja Party (BSP), 1949)
Bibliotheek François Vercammen
Titel op de kaft : In defence of October : the Copenhagen speech of November 1938
Engels
Brochure
Keywords: Trotski, Leon